Caracterização clínica, laboratorial e da composição de urólitos em felinos domésticos - Gomes, Veridiane da Rosa (2018)
The dissertation is divided into two chapters, the first one is a bibliographical review about urinary lithiasis in felines and the second chapter a scientific article reporting epidemiological, clinical and laboratory characterization of urolithiasis in felines. Urinay calculi of 42 felines attended in Veterinary teaching Hospital of Federal University of Goias (HV/EVZ/UFG) and other private veterinary clinics and hospitals were assessed using chemical analysis and energy dispersive spectroscopy (EDS). The most observed mineral was struvite (38,1%), followed by ammonium urate (35,7%) and calcium oxalate (26,2%). The males were more affected (26/42), as well mixedbreed animals (36/42). Animals aged between 25 and 72 months old were the most affected (27/42). In 33 cases (78,6%) the stones were recovered of bladder. The clinical signs with most occurrence were dysuria (65,0%), hematuria (50,0%), vomiting (17,5%) and anorexia (12,5%). Of the 42 felines studied, 39 (92.8%) were neutered. Regarding feeding, 26 (61.9%) cats received dry rations exclusively, while 13 (38.1%) received dry and wet rations. Despite the higher occurrence of struvite uroliths, a significant presence of ammonium urate uroliths was observed, which highlights the importance of studies on feline disease. The urolithiasis in cats is little studied in our country and the present work is a pioneer in the analysis of calculations in felines in Brazil, mainly due to the use of techniques of quantitative analysis, such as the dispersive energy spectroscopy.